Analisis Risiko Ergonomi dan Prevalensi Musculoskeletal Disorders (MSDs) pada Pekerja Kasir Menggunakan CMDQ dan REBA - Handayani, Sri Dewi; Suharyanto, Suharyanto (Dinasti Research, 2025)
Work-related musculoskeletal disorders (MSDs) are one of the leading causes of sick leave and disability in many countries. Cashier jobs have a high risk of MSDs due to static work postures and repetitive movements. Several studies have identified ergonomic risk factors in cashier workers but studies using CMDQ and REBA in analyzing the risk of MSDs in workers are still limited. This study aims to evaluate the prevalence and risk factors causing MSDs in cashier workers and identify the relationship of individual and occupational factors to MSDs complaints. This study involved 114 self-service cashier workers aged 18-55 years. Data were collected through the completion of demographic questionnaires, CMDQ forms and work posture analysis using REBA. REBA results show that 1.8% of workers have low risk, 77.2% of workers have work postures with moderate risk levels, 18.4% of workers have high risk, and 2.6% have very high risk so that further investigation and changes to posture are needed. Results from the CMDQ showed that the highest prevalence of pain was in the right leg (86.8%), left leg (84.2%), and lower back (76.3%). Significant risk factors included age (p = 2.781 x 10-8), length of service (p = 6.66 x 10-11), body mass index (p = 1.47 x 10-7), gender (p = 0.005), and work posture measured using REBA (p = 2.2 x 10-16). Kendall-Tau test also showed a positive relationship between these variables and MSDs complaints. This study shows that cashier workers with high work posture risk have a greater prevalence of MSDs. Multiple linear regression tests showed that the dominant factors causing MSDs complaints in cashier workers were posture and workstation height. Ergonomic recommendations are needed to reduce the risk of MSDs, especially for workers with high risk levels.